Analysis of the Effect of Soil Classification on Displacement and Inter-story Drift of Reinforced Concrete Buildings - Dermawan Zebua; Bimawijaya Laia; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The seismic performance of reinforced concrete (RC) shophouse buildings is strongly influenced by local soil conditions, which affect the amplification of ground motion and the dynamic response of structures during earthquakes. This study aims to analyze the effect of soil classification on displacement and inter-story drift in a reinforced concrete shophouse building subjected to seismic loading. A quantitative research approach was employed using Response Spectrum Analysis (RSA) in accordance with the provisions of SNI 1726:2019. The structural model was analyzed under three different soil classifications, namely Site Class SC (very dense soil), Site Class SD (medium soil), and Site Class SE (soft soil), while maintaining identical structural geometry, material properties, and loading conditions. The results indicate that soil classification significantly affects the seismic response of the building. The maximum roof displacement increased from 42.8 mm for Site Class SC to 76.9 mm for Site Class SE, representing an increase of 79.67%. Similarly, the maximum inter-story drift ratio increased from 0.72% to 1.42%, corresponding to an increase of 97.22%. The highest displacement and drift values were consistently observed under soft soil conditions due to greater seismic wave amplification and increased flexibility of the soil-structure system. Although all analyzed cases satisfied the drift limitations specified by SNI 1726:2019, buildings located on soft soil sites exhibited significantly higher deformation demands. The findings demonstrate that soil classification is a critical parameter in seismic design and should be carefully considered during the planning and analysis of reinforced concrete shophouse buildings to ensure structural safety and resilience in earthquake-prone regions.